Efektivitas Subsidi Energi Terhadap Pengendalian Inflasi Tahun 2019-2024 - Salwa Salsabila Amadya Azzuhria (CV. ITTC INDONESIA, 2025)
Energy subsidies are a key policy instrument for the Indonesian government to stabilize prices and mitigate inflationary pressures, especially during periods of crisis and global energy market volatility. This study aims to analyze the effectiveness of energy subsidies—particularly for fuel and electricity—in controlling national inflation from 2019 to 2024. Employing a literature review methodology, this research utilizes secondary data from Bank Indonesia (BI), Statistics Indonesia (BPS), the Ministry of Finance, and the Ministry of Energy and Mineral Resources, complemented by insights from Indonesian academic journals. The findings reveal that energy subsidies have played a significant role in curbing inflation spikes, particularly during critical periods such as the COVID-19 pandemic and the 2022 geopolitical conflict. However, the policy’s effectiveness is constrained by substantial fiscal burdens, inefficiencies in subsidy targeting, and potential distortions in budget allocation. Therefore, this study recommends reforming subsidy policies toward a more targeted system, integrated with fiscal and monetary policies to achieve more efficient and sustainable inflation control.